Bacterial flora associated with hatchery-reared juvenile giant tiger prawn, Penaeus monodon (fabricius), and screening of putative bacteria as probiotic candidate - Zadeh, Shahram Shakiba (2012)
Post larvae of giant tiger prawn, Penaeus monodon, was reared in Puchong hatchery complex of Universiti Putra Malaysia up to juvenile stage. Bacterial flora of different body parts, sediment and rearing water was determined using conventional biochemical methods and GN and GP Biolog microplate system. Highest amount of total bacterial count, total Vibrio count and total Pseudomonas count were observed in sediment followed by digestive system (hepatopancrease and intestine). Seven different genera were identified from different body parts, sediment and rearing water comprised of 72% Gram negative bacteria. The predominant bacteria were Vibrio followed by Shewanella, while incident of Shewanella in digestive system was considerably more than sediment, which is indirect evidence for its colonization in digestive system. Thereafter, antagonistic ability of bacterial flora isolates was examined against the most detrimental shrimp pathogens (Vibrio harveyi, Vibrio parahaemolyticus, and Vibrio alginolyticus) using well plate diffusion technique and cross streak technique. The largest inhibitory zones against mentioned shrimp pathogen were produced by Shewanella algae followed by Burkholderia glumae and Bravibacterium linens. Further antagonistic studies were conducted on S. algae in different pH, Salinity, temperature and time using Response Surface methodology. S.algae was able to induce its antagonistic ability against mentioned shrimp pathogens in relatively wide range of experimental conditions. Further observation on growth potential of the candidate probiotic, S. algae, in different pH, salinity, temperature and time was performed using RSM. The candidate probiotic was able to grow and produce anti-Vibrio substances in different environmental condition. Subsequently, the probiotic ability of the candidate probiotic in compare with 3 mentioned pathogens was assessed by means of a ranking index IR. Bacterium with shorter lag period, , and doubling time, dt, can overcome other bacteria in vivo. Candidate probiotic was faster than V. harveyi and V. algionolyticus but not faster than V. parahaemolyticus. The safety of candidate probiotic for tiger prawn was subsequently examined. Four treatments group of juvenile P. monodon were fed with 2 levels of candidate probiotic supplemented feed (107 and 1010 cfu/g), negative and positive controls for 3 weeks. The highest survival rate was observed in the 2nd treatment (1010 cfu/g) which was significantly different with controls. Low and high salinity stress tests and low temperature stress test were performed within treatment groups to evaluate the effect of candidate probiotic during stressful condition. The 2nd treatment (1010 cfu/g) exhibited significantly higher survival rate within treatments in all stress tests. Consequently, in vivo study of candidate probiotic was assessed through feeding shrimp treatment groups by supplementing commercial shrimp feed with 4 levels of candidate probiotic (T1; 104, T2; 107, T3; 1010 and T4; 1013 cfu/g). The significant highest feed conversion ratio, specific growth rate, protein efficiency ratio and survival was observed in 3rd treatment, this treatment consisted of significantly better bacterial balance and exhibited highest survival rate after 2 weeks challenging with V. harveyi. The possible human risk associated with using of S. algae was derived from lethal dose 50%, LD50, on mammalian model, BALB/C mice. LD50 of candidate probiotic was about 1036 via oral rout of administration which exhibited its safety for mammalian. Generally, S. algae exhibited quite good probiotic characteristics and can be introduced for further commercial and industrial studies.